Prognostic Significance of Plasma High‐Sensitivity C‐Reactive Protein in Patients With Hypertrophic Cardiomyopathy. Issue 2 (2nd February 2017) - Zhu, Ling; Zou, Yubao; Wang, Yilu; Luo, Xiaoliang; Sun, Kai; Wang, Hu; Jia, Lei; Liu, Yan; Zou, Juan; Yuan, Zuyi; Hui, Rutai; Kang, Lianming; et al.
Abstract : Background: Elevated high‐sensitivity C‐reactive protein (hsCRP) has been associated with increased risks of adverse outcomes of various cardiovascular diseases. The relationship between hsCRP and the prognosis of hypertrophic cardiomyopathy remains to be evaluated. Methods and Results: The study used an observational cohort methodology. A total of 490 patients were enrolled in the Fuwai Hospital from 2001 to 2011 and were followed for 3.7±2.0 years. According to the risk category of hsCRP, subjects in the high hsCRP group (>3.0 mg/L) had a higher risk of developing adverse events than the low hsCRP group (<1.0 mg/L): cardiovascular death (adjusted hazard ratios[HR] 5.41, 95% CI 1.96–14.93, P =0.001), all‐cause mortality (adjusted HR 4.78, 95% CI 1.99–11.47, P <0.001), sudden cardiac death (adjusted HR 11.29, 95% CI 1.38–92.20, P =0.024), and heart failure–related death (adjusted HR 4.38, 95% CI 1.15–16.60, P =0.030). Similarly, the continuous variable of hsCRP was also an independent predictor for adverse outcomes: cardiovascular death (adjusted HR 1.15, 95% CI 1.06–1.25, P =0.001), all‐cause mortality (adjusted HR 1.17, 95% CI 1.09–1.26, P <0.001), sudden cardiac death (adjusted HR 1.20, 95% CI 1.06–1.36, P =0.003), and heart failure–related death (adjusted HR 1.15, 95% CI 1.02–1.30, P =0.020). Conclusions: Our results indicate that elevated plasma hsCRP is associated with increased risk for adverse outcomes in patients with hypertrophic cardiomyopathy.